The Equipment Used in the SF6 Technique to Estimate Methane Emissions Has No Major Effect on Dairy Cow Behavior - Pereira, Fabiellen Cristina; Teixeira, Dayane Lemos; Boyle, Laura Ann; Pinheiro Machado Filho, Luiz Carlos; Williams, Shaun Richard Owen; Enriquez-Hidalgo, Daniel (Frontiers in Veterinary Science, 2021)
The natural behavior of animals can be disrupted by the techniques and materials of research methodologies. This study aimed to evaluate the effect of the equipment used in the SF6 tracer technique to estimate enteric methane emissions on the behavior of lactating dairy cows. Cows (n=24) were allocated to one of two diets: CONTROL and experimental diet (MIX). Behavior was assessed through video recordings between milking times during four phases: 3 days before fitting cows with the SF6 equipment (PRE); First 2 days after cows were fitted with the SF6 equipment (ADAP); 3 days during methane emission measurements (MEAS) ; and 2 days after the SF6 equipment removal (POST). Behaviors recorded included eating, ruminating or idling, resting and other. Affiliative or agonistic and discomfort behaviors (scratching or pushing the equipment) were also recorded. Lying time was recorded over 14 days using dataloggers fitted to the cows’ leg. Milk production and feed intake were recorded daily. MIX cows ruminated more than CONTROL cows (P = 0.05). Cows ruminated more at MEAS than in any other phase (P < 0.01). Time spent idling gradually decreased from PRE to MEAS for MIX cows (P < 0.01). Cows were lying down for longer in MEAS than in ADAP and POST (P < 0.01). Time spent lying with head down was shorter during PRE and ADAP than POST (P < 0.05). No difference was observed in the occurrence of discomfort or agonistic behaviors (P > 0.05). Affiliative behaviors occurred more often in ADAP than in MEAS (P < 0.05). There was no difference between phases in daily lying time, number of lying bouts per day or mean bout duration (P > 0.05). Milk production was not influenced by the SF6 equipment (P > 0.05). DMI was higher for CONTROL cows (P < 0.01) and it decreased from PRE to MEAS (P < 0.01). However, milk yield did not differ between cows wearing the SF6 equipment and those without it (P > 0.05). We conclude that SF6 equipment had minimal effect on dairy cow behavior.